African icons : ten people who shaped history - Baptiste, Tracey (Algonquin Young Readers, 2021)
Provides colorfully illustrated profiles of ten notable men and women in African history, from ancient times to the sixteenth century. Highlights kings, queens, inventors, scholars, and artists among others, and features maps and graphics for further learning.